1999
DOI: 10.1042/0264-6021:3430419
|View full text |Cite
|
Sign up to set email alerts
|

Common structural features determine the effectiveness of carvedilol, daunomycin and rolitetracycline as inhibitors of Alzheimer β-amyloid fibril formation

Abstract: One of the major pathological features of Alzheimer's disease is the deposition of beta-amyloid peptide (Abeta). Cellular toxicity has been shown to be associated with fibrillar forms of Abeta; preventing this fibril formation is therefore viewed as a possible method of slowing disease progression in Alzheimer's disease. With the use of a series of tetracyclic and carbazole-type compounds as inhibitors of Abeta fibril formation, we here describe a number of common structural features that seem to be associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 0 publications
3
91
0
2
Order By: Relevance
“…Initial structural analysis revealed that carvedilol, along with rolitetracycline and daunomycin, has a structural motif essential for binding to Aβ [115]. Subsequently, carvedilol was found to interfere with the oligomerization of Aβ [116].…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…Initial structural analysis revealed that carvedilol, along with rolitetracycline and daunomycin, has a structural motif essential for binding to Aβ [115]. Subsequently, carvedilol was found to interfere with the oligomerization of Aβ [116].…”
Section: Antihypertensive Drugsmentioning
confidence: 99%
“…Therefore, it was suggested (18) that RTC may be given intravenously or intramuscularly in serious bacterial infections when oral administration is not practicable. Although it is an antibiotic, it has been described (19) that RTC can effectively inhibit Ab fibril formation, which is associated with Alzheimer's disease. RTC has also been reported (20) to significantly inhibit the dengue virus propagation.…”
mentioning
confidence: 99%
“…3B). This IC 50 value, which is reflective of a combination of binding affinity and stoichiometry, might suggest that compound 2 acts by binding A␤ 1-40 monomers to prevent nucleation, as has been suggested for the inhibition of A␤ 1-40 monomer aggregation by daunomycin (Howlett et al, 1999a) and the inhibition of A␤ 1-42 monomer aggregation by rifamycin and hematin (Necula et al, 2007b). Alternatively, compound 2 may bind on-pathway aggregates to prevent their progression into mature fibrillar structures.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, small-molecule inhibitors have been observed to promote fibril formation but inhibit ongoing fibril growth (Williams et al, 2005) and to selectively inhibit different mechanisms of soluble aggregate growth (Moss et al, 2004). In addition, although some small molecules prevent both oligomer and fibril formation (Howlett et al, 1999a;De Felice et al, 2004;Yang et al, 2005;Bastianetto et al, 2006;Necula et al, 2007b), other inhibitors halt the appearance of oligomers without altering mature fibril formation (Necula et al, 2007a) or, conversely, block the appearance of mature fibrils while permitting oligomer formation (Lashuel et al, 2002;Ferrã o-Gonzales et al, 2005;Necula et al, 2007b). These qualitative studies demonstrate that small-molecule inhibitors of A␤ self-assembly can selectively act on various assembly pathways.…”
mentioning
confidence: 99%